2018
DOI: 10.1002/rth2.12061
|View full text |Cite
|
Sign up to set email alerts
|

Platelets at the vascular interface

Abstract: In this brief review paper, we will summarize the State-of-the-Art on how platelet reactivity is regulated in circulation and at sites of vascular injury. Our review discusses recent and ongoing work, presented at this year’s International Society on Thrombosis and Haemostasis (ISTH) meeting, on the role of platelets in (1) classical hemostasis at sites of mechanical injury, and (2) the maintenance of vascular integrity at sites of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
(128 reference statements)
0
18
0
Order By: Relevance
“…Platelets are specialized cells generated from the cytoplasmic fragmentation of megakaryocytes to ensure the integrity of the vascular system upon mechanical injury or any other vascular breach, occurring, for instance, at sites of inflammation. [1][2][3] Platelet stimulation triggers intracellular signaling cascades that promote cytoskeletal remodeling, secretion of granules, release of eicosanoids, and conversion of integrin receptors from a lowto a high-affinity state for their ligands (inside-out activation). Once active, integrins mediate platelet adhesion to the exposed extracellular matrix and aggregation to adjacent active platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are specialized cells generated from the cytoplasmic fragmentation of megakaryocytes to ensure the integrity of the vascular system upon mechanical injury or any other vascular breach, occurring, for instance, at sites of inflammation. [1][2][3] Platelet stimulation triggers intracellular signaling cascades that promote cytoskeletal remodeling, secretion of granules, release of eicosanoids, and conversion of integrin receptors from a lowto a high-affinity state for their ligands (inside-out activation). Once active, integrins mediate platelet adhesion to the exposed extracellular matrix and aggregation to adjacent active platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion is a rapid process that takes place within seconds of vascular injury and entails the deceleration of rapidly moving platelets to allow adherence to the vascular wall [52]. Owing to platelet margination by larger molecules, these cells are already in close proximity to the vascular endothelium and complexes can easily form between the platelet-specific receptors, such as glycoprotein (GP) Ib-V-IX, and the cell adhesion ligand von Willebrand factor (VWF), which acts as a bridge between the platelet surface and endothelial collagen [53].…”
Section: Platelet Function In Hemostasis and The Mechanisms Involvmentioning
confidence: 99%
“…Another important observation is that a positive charge on the surface of NPs can, in addition to warranting effective cellular drug delivery, also ensue immunotoxicity through the stimulation of inflammatory immune responses. Several researchers have found that cationic liposomes can stimulate neutrophils and induce oxidative bursts in these cells [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,...…”
Section: Leukocyte Function In Hemostasis and The Mechanisms Involmentioning
confidence: 99%
“…High-throughput profiling studies[14] identified among the most abundant signaling proteins in platelets (Table 1), the Ras-related protein (RAP) GTPases, a subset (5 members in mammals: RAP1A, RAP1B, RAP2A, RAP2B, RAP2C) of the larger RAS family that includes key regulators of cell adhesion, cytoskeleton remodelling and MAP kinase signaling[57]. These functions are critical for platelets that, in order to maintain the integrity of the vascular system, must be able to rapidly shift from an anti-adhesive/patrolling state to a pro-adhesive state, required to form a hemostatic plug and to prevent bleeding[8]. Indeed, studies by our group and others identified RAP GTPases as the critical molecular switches, which drive platelet activation at sites of vascular injury by switching on multiple platelet responses, including integrin inside-out activation, secretion, and eicosanoid mediator formation[913].…”
Section: Ras/rap Gtpases Expressed In Plateletsmentioning
confidence: 99%